2019
DOI: 10.1248/bpb.b18-00462
|View full text |Cite
|
Sign up to set email alerts
|

Cantharidin Attenuates the Proliferation and Migration of Vascular Smooth Muscle Cells through Suppressing Inflammatory Response

Abstract: Abnormal proliferation and migration of vascular smooth muscle cells (VSMCs) and the chronic inflammation regulated by various inflammatory factors are the major pathological processes in the development of neointimal hyperplasia and in-stent restenosis after angioplasty. Cantharidin is a potent and selective inhibitor of protein phosphatase 2A, which plays pivotal roles in cell cycle progression, cell fate, and inflammation. This study was to explore whether Cantharidin could inhibit VSMCs proliferation, migr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Modern studies have found that many drugs can induce hepatotoxicity through ERS such as paracetamol and anti‐type 2 diabetes drugs (ciglitazone and troglitazone), and some TCMs including Polygonum multiflorum , Matrine, psoralea, and Coptis chinensis have been reported to induce hepatotoxicity in association with ERS (Liu, Li, & Zhang, 2019). Furthermore, ERS can mediate autophagy and apoptosis based on unfolded protein response (UPR), calcium signaling, and tumor protein p53 (P53) signaling, and accumulation of unfolded or misfolded proteins in the ER leads to UPR, which are important in cellular self‐defense (Li et al, 2010; Qiu et al, 2019; Tian, Zeng, Li, Wu, & Wang, 2015; Wang, Chow, Chien, & Lin, 2018; Xi et al, 2015). These two processes have also been reported to play an important role in drug‐induced hepatotoxicity (Yongke & Arthur, 2015; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Modern studies have found that many drugs can induce hepatotoxicity through ERS such as paracetamol and anti‐type 2 diabetes drugs (ciglitazone and troglitazone), and some TCMs including Polygonum multiflorum , Matrine, psoralea, and Coptis chinensis have been reported to induce hepatotoxicity in association with ERS (Liu, Li, & Zhang, 2019). Furthermore, ERS can mediate autophagy and apoptosis based on unfolded protein response (UPR), calcium signaling, and tumor protein p53 (P53) signaling, and accumulation of unfolded or misfolded proteins in the ER leads to UPR, which are important in cellular self‐defense (Li et al, 2010; Qiu et al, 2019; Tian, Zeng, Li, Wu, & Wang, 2015; Wang, Chow, Chien, & Lin, 2018; Xi et al, 2015). These two processes have also been reported to play an important role in drug‐induced hepatotoxicity (Yongke & Arthur, 2015; Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, overexpression of miR-7 significantly increased the expression of p21 in VSMCs induced by Hcy, while decreased the expression of CyclinD1 and VEGF, suggesting that miR-7 inhibited the proliferation and migration of VSMCs by activating p21 and E-cadherin expression and inhibiting CyclinD1 and VEGF. In addition to the abnormal proliferation and migration of VSMCs, chronic inflammation mediated by inflammatory factors such as IL-6 and TNF-α is the main pathological process of neointimal hyperplasia, in-stent restenosis and the development of AS after angioplasty (15). In this study, it was found that overexpression of miR-7 significantly decreased the expression of IL-6 and TNF-α genes, and inhibited the inflammatory response of VSMCs induced by Hcy.…”
Section: Discussionmentioning
confidence: 61%
“…Cell viability was assessed with the CCK-8 assay as described previously [22]. Briefly, H9c2 cells were seeded in 96-well plates at a density of 10,000 cells per well in 100 µL culture medium.…”
Section: Cck-8 Assaymentioning
confidence: 99%